2011
DOI: 10.1099/mic.0.048314-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of Streptococcus mutans towards friend and foe in mixed-species cultures

Abstract: In the oral biofilm, the 'mitis' streptococci are among the first group of organisms to colonize the tooth surface. Their proliferation is thought to be an important factor required for antagonizing the growth of cariogenic species such as Streptococcus mutans. In this study, we used a threespecies mixed culture to demonstrate that another ubiquitous early colonizing species, Veillonella parvula, can greatly affect the outcome of the competition between a pair of antagonists such as S. mutans and Streptococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…In Streptococcus mutans, the causative agent of tooth decay, mutations in virulence or global regulatory genes (including genes involved in stress responses) strongly affect gene transcription (81)(82)(83)(84)(85), including that of the type II cas genes ( Fig. 1 and 4).…”
Section: Transcriptome Analysis Of the Cas Genesmentioning
confidence: 99%
“…In Streptococcus mutans, the causative agent of tooth decay, mutations in virulence or global regulatory genes (including genes involved in stress responses) strongly affect gene transcription (81)(82)(83)(84)(85), including that of the type II cas genes ( Fig. 1 and 4).…”
Section: Transcriptome Analysis Of the Cas Genesmentioning
confidence: 99%
“…However, there are instances when bacteria living in these communities are in direct conflict. Within these polymicrobial environments several factors can influence the balance of power between microbes, including bacterial self-defence weapons such as bacteriocins, secondary metabolites or H 2 O 2 (Kreth et al, 2008;Liu et al, 2011). Interestingly, host-derived nutrients can also play a role in promoting bacterial competition, as in the case of oral commensal streptococci and Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been demonstrated that the metabolism of yeast can be transformed by bacteria-induced prions to decrease the release of inhibiting ethanol (7). In another study, an oral biofilm of the genus Streptococcus displayed different transcriptional responses toward the presence of other species in mixed-species cultures (8).…”
mentioning
confidence: 99%